Pendugaan Produksi Karkas Dan Daging Kelelawar Pemakan Buah (Pteropus alecto ) Asal Sulawesi (ESTIMATION OF CARCASS AND MEAT PRODUCTION OF CELEBES NATIVE FRUIT BATS (Pteropus alecto)) - Ransaleleh, Tiltje Andretha; Maheswari, Rarah Ratih Adjie; Sugita, Purwantiningsih; Manalu, Wasmen (Jurnal Veteriner, 2014)
The study was conducted in North Sulawesi, Gorontalo, and Central Sulawesi during March untilOctober 2011. The purpose of this study was to determine the potential of fruit bats  (P. alecto) as sourceof meat. Observed variables were body weight, carcass weight, noncarcass weight, the bone weight, meatweight, fat weight, and skin weight, respectively. To estimate the growth rate of the bats, analysis of therelationship between body weight and carcass components was done, while estimation of  growth rate ofcarcass components were analyzed by multiple linear regression. The results showed that the carcassproduction of  P. alecto in the three locations was 54.49%-56.55%, meat production was 45.37% -54.07%,and the coefficient of determination was 0.65-0.99.  Conclusions of this study is that the body weight  canbe used for  prediction  of growth rate, and weight of carcass, meat, bone, fat, and skin of the fruit bats,respectively.
Keywords: meat of fruit eating bat, P. alecto